Role of Nano-silver and the Bacterial Strain Enterobacter cloacae in Increasing Vase Life of Cut Carnation ‘Omea’ - Naing, Aung H.; Win, Nay M.; Han, Jeung-Sul; Lim, Ki B.; Kim, Chang K. (Frontiers in Plant Science, 2017)
We investigated the role of nano-silver (NAg) and the bacterial strain Enterobacter cloacae in increasing the vase life of cut carnation flowers ‘Omea.’ NAg treatment extended vase life of the flowers by increasing relative fresh weight, antioxidant activities, and expression level of the cysteine proteinase inhibitor gene (DcCPi), and by suppressing bacterial blockage in stem segments, ethylene production and expression of ethylene biosynthesis genes and DcCP1 gene, compared with the control. Out of all the treatments, administration of 25 mg L-1 NAg gave the best results for all the analyzed parameters. Interestingly, application of E. cloacae also extended the vase life of cut flowers by 3 days in comparison with control flowers, and overall, showed better results than the control for all the analyzed parameters. Taken together, these results demonstrate the positive role of NAg and E. cloacae in increasing the longevity of cut carnation flowers, and indicate that this effect is brought about through multiple modes of action.